Removal of Histamine in Fish Sauce by Staphylococcus debuckii sp. Isolated from Fermented Fish - Natthakan Rungraeng; Kazuhisa Ohtaguchi; Teerin Chysirichote (Food Technology and Biotechnology, 2023)
Research background: One of the issues in the production of fish sauce is the legal constraints on the concentration of histamine produced by bacteria during fermentation because it causes allergic reactions in humans. The goal of this study is therefore to eliminate histamine from the final product after fermentation to enhance the quality of fish sauce for consumer safety, manufacturer exportability and domestic sales. Experimental approach: The bacteria that grow in the histamine medium were isolated from the salted fish. Their ability to degrade histamine in the media with high NaCl content was tested. The bacterium with the highest histamine-degrading ability was identified and the histamine-degrading conditions were optimized, including the incubation temperature and the amount of NaCl in the medium. The regression equation was generated and tested using the local fish sauce in which different concentrations of histamine were added. Results and conclusions: , the isolated histamine-degrading bacteria, could be used as an inoculum to reduce histamine accumulated in fish products. Novelty and scientific contribution: The microbiological technique developed here can decrease the histamine concentration in the final product, fish sauce, to improve its quality in terms of food safety and satisfy the histamine regulation requirement. The findings of this study can also be used to treat other liquid foods that contain high concentrations of histamine.
Keywords: Polyamine Metabolism and Applications; Biopolymer Synthesis and Applications; Bacterial biofilms and quorum sensing